Intravenous lidocaine’s function in preventing persistent post-operative pain - Luís M. F. Ramos (Research and Practice in Anesthesiology, 2024)
Background and Goal of Study Chronic post-operative pain (CPOP) is an increasing public health issue considering its impact on the patients quality of life and and the associated costs for the healthcare system. The incidence of CPOP can be as high as 75%, depending on the surgical procedure and other factors. Lidocaine is a local anesthetic with anti-inflammatory, analgesic and antihyperalgesic properties. Several studies have shown its use in controlling acute post-operative pain when used intravenously. The goal of this study was to define the role of intravenous lidocaine in preventing CPOP. Materials and Methods The PubMed database was searched from 2006 and 2019 with the keywords: “Chronic post-operative pain” or “Chronic post-surgical pain” or “Chronic pain” and “Intravenous lidocaine”. Adequate papers for the purpose of this study were selected. Results and Discussion Three randomized controlled trials that met criteria were obtained: two on breast surgery and the other on open nephrectomy. All trials used intravenous lidocaine during surgery, suspending the infusion up to the first 24-hours of the post-operative period. All three of them showed a significant decrease on the incidence of CPOP. There was a 20-fold decrease six months after breast surgery. Conclusion Intravenous lidocaine seems to decrease the incidence of CPOP however, there is limited evidence. More trials are necessary to define the efficacy and safety of intravenous lidocaine. A generally accepted definition of CPOP is needed.